Simply fly : a deccan odyssey - Gopinath, G. R. (Noida : Collins Business, 2009)
Autobiography of G.R. Gopinath, b. 1951, founder of Air Deccan, India's first low-cost airline.
Includes index.
Keywords: Gopinath, G. R., -- 1951-; Air Deccan (Airlines : India) -- Biography; Businesspeople -- India -- Biography; Aircraft industry -- India -- Biography; Airlines -- Cost of operation -- India